Student–teacher relationships and academic performance as predictors of subjective well-being among senior high school students - Qori Anisa Putri; Asri Mutiara Putri; Elsy Junilia (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Student subjective well-being (SSWB) reflects how students evaluate their quality of life at school. Student-teacher relationships and academic performance are important factors that may contribute to students’ subjective well-being. Purpose: To examine whether student–teacher relationships and academic performance predict subjective well-being among senior high school students, both simultaneously and individually. Method: A descriptive-analytical cross-sectional design and multiple linear regression analysis. The study was conducted at Senior High School 1 Padang Cermin, Pesawaran Regency, Lampung Province, Indonesia, with data collected offline on 10 April 2026. The accessible population comprised 623 active students in Grades X and XI from a total school enrolment of 932 students across Grades X–XII; Grade XII students were not included because they were no longer engaged in active classroom learning. A total of 254 students participated through quota sampling based on grade level, with the final sample comprising 128 Grade X (50.4%) and 126 Grade XI (49.6%) students. The sample size was not derived from a named Slovin, Cochran, or G*Power calculation; rather, it was justified by the adequacy of the sample for multivariate analysis and the number of eligible students accessible during data collection. Data were collected using the SSWQ, S-TSRI, and Academic Performance Scale. Results: Student–teacher relationships and academic performance jointly predicted subjective well-being, explaining 16.9% of its variance, F = 26.775, p < .001. Academic performance was a significant individual predictor, β = .408, t = 7.062, p < .001, whereas student–teacher relationships were not, β = .060, t = 1.037, p = .301. Conclusion: Academic performance significantly predicted students’ subjective well-being, whereas student–teacher relationships did not make a significant unique contribution after academic performance was included in the model. Keywords: Academic Performance; Senior High School Students; Student Subjective Well-Being; Student Teacher Relationships.